An introduction to 5G : the new radio, 5G network and beyond - Cox, Christopher (Christopher Ian), 1965- (John Wiley & Sons, Inc., 2021)
"This book is an introductory system-level guide to 5G, a market niche that existing books on 5G do not appear to address. By reading the book, readers will understand the architecture of 5G, the techniques used for radio transmission and reception, and the overall operation of the system. They will then be able to tackle the specifications and more advanced books with confidence."--